Multi-criteria decision analysis of energy system transformation pathways: A case study for Switzerland. (July 2017) - Volkart, Kathrin; Weidmann, Nicolas; Bauer, Christian; Hirschberg, Stefan
Abstract: Two recent political decisions are expected to frame the development of the Swiss energy system in the coming decades: the nuclear phase-out and the greenhouse gas (GHG) emission reduction target. To accomplish both of them, low-carbon technologies based on renewable energy and Carbon Capture and Storage (CCS) are expected to gain importance. The objective of the present work is to support prospective Swiss energy policy-making by providing a detailed sustainability analysis of possible energy system transformation pathways. For this purpose, the results of the scenario quantification with an energy system model are coupled with multi-criteria sustainability analysis. Two climate protection and one reference scenario are addressed, and the trade-offs between the scenarios are analysed based on a set of 12 interdisciplinary indicators. Implementing a stringent climate policy in Switzerland is associated with co-benefits such as less fossil resource use, less fatalities in severe accidents in the energy sector, less societal conflicts and higher resource autonomy. The availability and implementation of CCS allows for achieving the GHG emission reduction target at lower costs, but at the expense of a more fossil fuel-based energy system. Highlights: Three energy system transformation pathways for Switzerland are analysed. A set of policy-relevant sustainability indicators are quantified for each pathway. Implementing a stringent climate policy in Switzerland is associated with co-benefits. In the CCS scenario fossil fuel use increases, but the total system costs are lower. Fossil-fuelled transport substantially contributes to most of the addressed criteria.